Hubungan Financial Literacy dan Financial Knowledge Terhadap Keputusan Investasi Oleh Investor Pemula di Kota Bengkulu - Merita Tri Resky; Asnaini Asnaini; Debby Arisandi (UNIVED Press, 2023)
This research was conducted in order to see the relationship between financial literacy and financial knowledge on investment decisions by novice investors in the city of Bengkulu. This research is a quantitative research with a descriptive format and uses primary data. Data was collected from questionnaires distributed to respondents, there were 481 respondents who participated however, only 385 respondents who met the criteria. The sampling technique uses the slovin formula and purposive sampling. The results of this study indicate that financial literacy and financial knowledge have a positive and significant effect on investment decisions by novice investors in the city of Bengkulu with a Correlation Coefficient value for financial literacy of 0.761 which means it is very strong because it is in the range 0.76-0.99 and financial knowledge is 0.829 which means also in the range of 0.76-0.99 which means very strong.